Laparoscopic fundoplication and new aspects of neural anatomy at the oesophagogastric junction. Issue 3 (5th March 2020) - Gehwolf, P; Renz, O; Brenner, E; Cardini, B; Lorenz, A; Wykypiel, H
Abstract: Background: In fundoplication, mobilization of the distal oesophagus and proximal stomach is essential to obtain a sufficient tension-free intra-abdominal oesophageal length for creation of an efficient antireflux barrier. Most surgical literature and anatomical illustrations do not describe nerve branches running from the diaphragm to the stomach. After observing small nerve branches at laparoscopic fundoplication, penetrating the left crus of the diaphragm lateral to the hiatus and apparently running into the stomach, an anatomical cadaver study was undertaken to identify the origin and target organ of these nerves. Methods: Fifty-three human cadavers (23 men, 30 women; age range 35–103 years) were dissected with special attention to the nerves that penetrate the left crus of the diaphragm. The entire course of these nerves was documented with standardized drawings and photos. Results: Small nerve branches penetrating the diaphragm lateral to the left crus of the hiatus were found in 17 (32 per cent) of the 53 cadavers. In 14 of these 17 cadavers, one or two splanchnic nerve branches were identified, and in ten of the 17 the nerve branches were found to be phrenic nerves. In seven of these 17 cadavers, two different nerve branches were found and assigned to both splanchnic and phrenic nerves. Conclusion: Nerves penetrating the left crus with splanchnic origin or phrenic origin have been identified. Their function remains unclear and their relationship to postfundoplication symptoms remains to be determined. Graphical Abstract: Small nerve branches penetrating the left crus of the diaphragm lateral to the hiatus, presumably running into the stomach, were observed during surgery. These nerve branches were allocated to the splanchnic and phrenic nerves. The origins and target organs of these nerves were identified. Their role in postfundoplication complaints is discussed. Nerves that might influence outcome.